ANALISIS PENGGUNAAN FINTECH SYARIAH TERHADAP PENGEMBANGAN UMKM BERBASIS HALAL - Puti Khairani Rijadi; Triana Zuhrotun Aulia; Azhar Azhar; Sulaiman Efendi Siregar; Syahril Syahril (POLITEKNIK LP3I JAKARTA, 2026)
The development of digital financial technology has encouraged the emergence of Islamic fintech as an alternative financial service that aligns with Islamic principles. The presence of Islamic fintech is one solution to address various problems faced by Micro, Small, and Medium Enterprises (MSMEs), particularly halal-based MSMEs, which often experience limited access to financing and financial services. This study aims to analyze the use of Islamic fintech in the development of halal-based MSMEs and identify the benefits and challenges faced in its utilization. The study used a qualitative approach with a descriptive research type. Data were collected through in-depth interviews, observation, and documentation of halal-based MSMEs utilizing Islamic fintech services. Data analysis was carried out through data reduction, data presentation, and conclusion drawing using triangulation techniques to ensure data validity. The results show that Islamic fintech makes a positive contribution to the development of halal-based MSMEs through easier access to financing, accelerated transaction processes, increased financial management efficiency, and expanded market opportunities. The use of transparent and usury-free Islamic contracts is a key factor encouraging MSMEs to utilize Islamic fintech services. Furthermore, Islamic fintech plays a role in strengthening the halal economic ecosystem by more effectively connecting the Islamic financial sector and the real sector. However, the utilization of Islamic fintech still faces various obstacles, such as low digital and Islamic financial literacy, limited technological infrastructure, and concerns about the security of digital transactions. Therefore, increased education, strengthened regulations, and digital infrastructure development are needed to optimize the role of Islamic fintech in supporting the growth of halal-based MSMEs. This study concludes that Islamic fintech has significant potential as an economic empowerment instrument that can increase the competitiveness and desire of halal MSMEs in Indonesia.